Kubernetes for serverless applications : implement FaaS by effectively deploying, managing, monitoring, and orchestrating serverless applications using Kubernetes /: implement FaaS by effectively deploying, managing, monitoring, and orchestrating serverless applications using Kubernetes. (2018) - McKendrick, Russ
No abstract available